2010
DOI: 10.2105/ajph.2009.168831
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention and Diabetes Screening at Local Health Departments

Abstract: The presence of obesity prevention and diabetes screening programs was significantly associated with LHD structural capacity and general performance. However, the effectiveness and cost-effectiveness of both types of programs remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 28 publications
2
45
0
1
Order By: Relevance
“…Among the service types performed less frequently in small/rural jurisdictions compared with larger/urban jurisdictions were early and periodic screening, diagnostic, and treatment services for infants and children (48), other maternal and child health functions (85), access to medical care (81), access to dental care (81), and behavioral health services (81). One study found that obesity prevention programs were performed less frequently in smaller jurisdictions (125), whereas another found no significant difference in obesity and diabetes programming by rurality or population size (148). Smaller jurisdictions were also less likely to delegate or privatize services compared with large jurisdictions (63,64).…”
Section: Health Service Provisionmentioning
confidence: 99%
“…Among the service types performed less frequently in small/rural jurisdictions compared with larger/urban jurisdictions were early and periodic screening, diagnostic, and treatment services for infants and children (48), other maternal and child health functions (85), access to medical care (81), access to dental care (81), and behavioral health services (81). One study found that obesity prevention programs were performed less frequently in smaller jurisdictions (125), whereas another found no significant difference in obesity and diabetes programming by rurality or population size (148). Smaller jurisdictions were also less likely to delegate or privatize services compared with large jurisdictions (63,64).…”
Section: Health Service Provisionmentioning
confidence: 99%
“…Zhang et al [33] identified about half of health departments offer diabetes screening, which is consistent with the 2008 National Profile of Local Health Departments report that 46 % of health departments screened for diabetes [22]. Zhang et al [33] study provided valuable insight on diabetes screening programs; all reporting health departments identified the need for screening algorithms, education, and referral options. Guidelines for health departments were recognized as a potentially useful tool [33].…”
Section: Consequences Of Missed Diagnosismentioning
confidence: 58%
“…Historically, health departments have been synonymous with infectious disease control; however their scope has broadened to meet public health needs. An epidemiological shift has occurred, with lessening threats of infectious disease, and an increasing prevalence of chronic disease, including prediabetes and diabetes [16,33]. With a growing prevalence of obesity and diabetes, particularly amongst the disadvantaged, health departments will continue to serve as a point of care, however further investigation on expanding this role is warranted [33].…”
Section: Consequences Of Missed Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…community health outcomes. 20 In addition, previous studies have investigated overall level of provision of obesity prevention and control in jurisdictions, 21,22 but little is known about what types of services have been provided and whether there are any changes in provision of these services over time. The objectives of this study are to describe and compare the provision of the 10 EPHS for obesity control by LHDs in 2005 and 2008 and explore factors that are associated with providing these services.…”
mentioning
confidence: 99%